Responses of 11th Grade Students to the Implementation of Innovative Methods and Media in Mathematics Learning during Teaching Assistance Activities - Avinda Dwi Sagita; Imam Rofiki; Dharmendra Kumar Yadav (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to describe the response of students in class XI to the application of innovative methods and media in learning mathematics in teaching assistance activities at SMA Negeri 1 Batu. The background of this study is the low motivation of students to learn caused by the lack of variety in learning methods and media. The approach used in this descriptive research is a qualitative, with a subject of 36 students (13 male students and 23 female students) in class XI. Data were collected through validated questionnaires and structured interviews. The results of the analysis showed that students gave a positive response, with a score of , to the application of the discovery learning model, independent learning, the use of student worksheets, and interactive media such as Quizizz and snakes and ladders games. These innovations encourage students to be more active, motivated, and assisted in understanding mathematical concepts. Overall, the findings of this study indicate that the application of method and media innovations in teaching assistance activities can increase student involvement and understanding in learning mathematics in a more meaningful and enjoyable way.